Notch Band Switchable Reconfigurable Monopole Antenna with Defected Ground Structure for Wideband Applications - Lokesh Raju, V; Rajya Lakshmi, V; S Anuradha, M (International Journal of Engineering and Technology, 2018)
A compact notch band switchable antenna with defected ground structure is proposed in this article. The designed antenna is constructed on FR4 substrate of Ær=4.4 with overall dimension of 26X24X1.6 mm. The patch consisting of square shaped radiating element with corner truncation at lower edges. Two inverted U-shaped slots are placed on the radiating element to achieve the notch band characteristics in the antenna operating band. The proposed antenna covering operating bands from 3.7 to 7.9 GHz and 11.3 to 20 GHz with impedance bandwidth of 71% and 67% respectively. The antenna providing peak realized gain of 5 dB and efficiency more than 85% in the operating band. The frequency reconfigurable behaviour of the antenna with diodes switching is presented in this article. A perfect correlation between the results on Anritsu combinational analyzer MS2037C and HFSS simulation witness the applicability of this antenna in wideband communication applications.Â Â